THE INFLUENCE OF BRAND INTERACTIVITY, INVOLVEMENT, SOCIAL MEDIA CBE ON LOYALTY: TRUST AS A MEDIATION VARIABLE - Cahyadi, Febrianne Clarissa; Tunjungsari, Hetty Karunia (Graduate Program of Universitas Tarumanagara, 2023)
Previous research conducted by Samarah (2021) [8] found that brand interactivity and brand engagement had an effect on social media customer brand engagement. In addition, social media customer brand engagement has an effect on brand loyalty, both directly and through the brand trust mediation variable. Meanwhile, research conducted by Li et. al (2020) [9] revealed that customer engagement has an effect on brand attachment and brand trust, then brand attachment and brand trust have an effect on brand loyalty. However, in this study it was found that customer involvement did not directly affect brand loyalty. This study aims to examine the effect of brand interactivity, brand involvement, and social media consumer brand engagement on brand loyalty. Then to test the effect of brand trust as a mediation between brand engagement and brand loyalty. The study used 240 samples selected using purposive sampling technique and analyzed using PLS-SEM. The results of this study indicate that brand interactivity, brand involvement, and social media consumer brand engagement have effects on brand loyalty. This research also shows that brand trust mediates the effect of brand engagement on brand loyalty. From this research, brand involvement has the biggest direct effect on brand loyalty. This shows that Tokopedia must continue to maintain interactivity, involvement, engagement, and trust so that consumers are increasingly loyal to the company.